Alterations in the Serum Trace Element Levels in Women Infected with Chlamydia Trachomatis (UKH Journal of Science and Engineering, 2020)
Most infectious diseases are accompanied by changes in the levels of several trace elements in the blood. A total of 88 female patients referred to the Nawroz Private Laboratory in the Duhok province, Kurdistan Region, Iraq, were enrolled in this study. The enrolled patients were sent to the laboratory for investigation of their hormone levels because they were suffering from various gynecologic abnormalities. The serum levels of anti-chlamydia immunoglobulin (Ig) G and IgM antibodies were estimated using enzyme-linked immunosorbent assay (ELISA) tests, and the serum trace element levels were evaluated by atomic absorption spectroscopy.The results showed that 10 (11.4 %) of the samples tested positive for the presence of anti-chlamydia IgG antibodies, whereas none of the samples tested positive for anti-chlamydia IgM antibodies. Furthermore, a significant reduction in the serum potassium levels was observed in response to the chlamydia infection, whereas no signiﬁcant changes were observed in any of the other elements.